Adult soft tissue sarcoma and time to treatment initiation: An analysis of the National Cancer Database. Issue 8 (27th June 2018) - Curtis, Gannon L.; Lawrenz, Joshua M.; George, Jaiben; Styron, Joe F.; Scott, Jacob; Shah, Chirag; Shepard, Dale R.; Rubin, Brian; Nystrom, Lukas M.; Mesko, Nathan W.
Abstract : Background: The primary goal of this investigation is to determine the current national standards for time to treatment initiation (TTI) in soft tissue sarcoma (STS). Additionally, we aim to identify the variables affecting TTI variability in STS. Methods: An analysis of the National Cancer Database identified 41 529 patients diagnosed with STS between 2004 and 2013. Kruskall‐Wallis tests identified differences between covariates regarding TTI. Negative binomial regression models identified variables that independently influenced TTI, and adjusted for confounders. Results: The median TTI was 22.0 days and the mean TTI was 29.7 days. Longer TTI was correlated with transitions in care between institutions (Incidence rate ratio [IRR] = 1.76; P < 0.001), neoadjuvant radiotherapy (IRR = 1.53; P < 0.001), neoadjuvant systemic therapy (IRR = 1.40; P < 0.001), treatment at an academic center (IRR = 1.23; P < 0.001), Medicaid (IRR = 1.18; P < 0.001), being uninsured (IRR = 1.13; P = 0.001), and Medicare (IRR = 1.05 P = 0.016) status. Shorter TTI was correlated with tumor size >5 cm (IRR = 0.93; P < 0.001), high grade (IRR = 0.92; P = 0.015), truncal tumor site (IRR = 0.94; P = 0.003), and median income >63 000 (IRR = 0.95; P = 0.028). Conclusions: The median TTI in the United States for STS is 22 days. Increased TTI in STS are associated with tumor and treatment characteristics, socio‐economic factors and hospital systems issues. Transitions in care between institutions are responsible for the greatest increases.